1964
DOI: 10.1083/jcb.23.3.431
|View full text |Cite
|
Sign up to set email alerts
|

ELECTRON MICROSCOPE STUDY OF SPERMIOGENESIS IN A FIRE-BRAT INSECT, THERMOBIA DOMESTICA PACK

Abstract: The fine structure of the mature spermatozoon of the insect Thermobia domestica has been investigated. This flagellate spermatozoon is unique with respect to the relative positions of the centriole, nucleus, mitochondrial nebenkern derivatives, and acrosome along the length of the cell. The acrosome lies at the posterior end of the nucleus. Unlike spermatozoa of most animals, the Thermobia spermatozoon has a nucleus that reveals an unusual lamellar pattern of the material inside of it. ~[his flagellate spermat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1966
1966
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…In the sperm tail (Fig. 3) the tubular fibers of the outermost ring have the same structure as the two in the center, and similar fibers have been reported to occur in two unrelated insects (7,8). It is, therefore, tantalizing that the fibers in the sperm of yet another insect, Acheta domestica (9), are composed, not of concentric rings, but of ten outer fibrils arranged around four inner.…”
Section: Discussionsupporting
confidence: 57%
“…In the sperm tail (Fig. 3) the tubular fibers of the outermost ring have the same structure as the two in the center, and similar fibers have been reported to occur in two unrelated insects (7,8). It is, therefore, tantalizing that the fibers in the sperm of yet another insect, Acheta domestica (9), are composed, not of concentric rings, but of ten outer fibrils arranged around four inner.…”
Section: Discussionsupporting
confidence: 57%
“…There are numerous examples in the literature of highly ordered arrays of microtubules. Reported studies include: the axostyle of certain flagellates (25, 26, 8, 29, 41, and 39); the axopods of heliozoa (34,31,35,58,57,59,56,48,49,52,55); the tentacles of suctoria (50,3); the cytopharyngial basket of some ciliates (60,61,62); the cortical fibers in other ciliates (2, 35 a, 32); transient structures in a variety of spermatids (10,40,46,18); permanent structures in other sperm (5,44,45,47); and the ubiquitous 9 -t-2 structure of cilia and flagella (19, 23, i, 51, 43, 30, 63, 64, 65). Studies on each of these systems have revealed thin bridges between the component microtubules.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubules surrounding the nuclei of sperm cells have been observed in many animals; in most of these cases they disappear at maturity (Nagano 1962, Bawa 1964, Anderson et al 1966, 67, Kessel 1966, 67, 70, Werner 1966, McIntosh and Porter 1967, Postwald 1967, Reger 1967, Hoage and Kessel 1968, Mattei et al 1972, Stanley et al 1972, but in some other cases they are still present in the mature sperm cells (Reger 1963, Rosario 1964, Silveira and Porter 1964, Bonsdorff and Telkka 1965, Makielski 1966, Phillips 1966.…”
Section: Discussionmentioning
confidence: 99%